Medium optimization for biosurfactant production by Rhodococcus ruber TD2 using response surface methodology - Nga, Vuong Thi; Hoa, Kieu Quynh; Man, Tran Dinh; Hien, Lai Thuy (Academia Journal of Biology, 2015)
With the advanced properties such as excellent emulsifying activity, reducing surface tension, antitumor and immunomodulation, Rhodococcus biosurfactants have attracted a great deal of interest from biologists community. Development of optimized procedures for their biosynthesis would increased application potentials of Rhodococcus biosurfactants in new advanced technologies, such as environmental bioremediation, biomedicine, etc. The goal of this study is to determine the medium optimization for biosurfactant production by Rhodococcus ruber TD2 using response surface methodology (RSM) based on changes of medium component: diesel oil (DO), NaNO3 and pH. All of three factors were the most significant influences on its biosurfactant biosynthesis. RSM analysis showed that the highest biosurfactant production was achieved with medium containing 5.7% (v/v) DO, 3.3 gL-1 NaNO3 and pH 8.3. In this condition, strain TD2 produced maximum yield of crude biosurfactant, which was 30.1 gL-1 after 5 days. This value was 2.23- fold higher than before medium optimization. The data showed that RSM was highly efficient in optimizing biosurfactant production by Rhodococcus ruber TD2 isolated from coastal zone of Vietnam.